Pengaruh Pemberian Ekstrak Belut (Monopterus albus) pada Penyembuhan Luka Bakar Tikus Putih Jantan Sprague-Dawley - Dwi Mulyani; Febriyenti Febriyenti; Almahdy Almahdy (Jurnal Sains Farmasi & Klinis, 2016)
The aim of this investigation was a clinical evaluation of the accelerating effect of Monopterus albus extract on the burn wound healing in male Sprague-Dawley rats weighted 200-300. The sample then extracted using wet rendering method using aqua-dest as extractor. This was experimental research with posttest only control group design. The subjects were ten male Sprague-Dawley rats devided into two group (control group 1 and experimental group 2). Every group consist of five rats. Heated metal plat (2cm x 2cm) used to get full thickness burn wound on dorsal rat part. Then, Monopterus albus extract was given to group 2 for 20 days. The results showed that Monopterus albus extract have significant effect (p < 0,05) to wound healing of rat models.